Moderating Role of Community Participation on Performance of Affordable Housing Program in Kenya (Global Journal of Management and Business Research, 2020)
It is estimated that the current affordable housing deficit stands at 2 million houses with nearly 61% of urban households living in slums. This deficit continues to rise due to fundamental constraints on both the demand and supply side and is exacerbated by an urbanization rate of 4.2%, equivalent to 0.5 million new city dwellers every year. The study intended to examine how project management triple constraints and performance of affordable housing program in Kenya.
Keywords: scope management; time management; community participation